A CORPUS-BASED STUDY OF JOKO WIDODO’S REPRESENTATION IN THAI MEDIAS - Wijaya, Debi Pangestuti (Direktorat Pendidikan dan Internasionalisasi, 2025)
The present research examines how Joko Widodo is represented in Thai media by analyzing the semantic prosody linked to his name and exploring the linguistic framing employed by the Thai media. This research employs a mixed-method research design. The quantitative method identifies word frequency, whereas the qualitative method describes semantics prosody. The self-constructed corpus of this research includes articles from the Bangkok Post and the Nation Thailand, two widely known Thai media, analyzed using Sketch Engine software. In this research, ten collocates for “Jokowi”, “Joko Widodo”, and “Mr Widodo” were identified. From the semantic prosody investigation, “Mr Widodo” tends to have neutral to positive semantic prosody; “Jokowi” tends to have neutral to negative, and “Joko Widodo” has mixed semantic prosody with neutral, positive, and some negative meanings.